Geospatial analysis of type B and C hepatitis in South Sulawesi - Rachmawarni Bachtiar, Rini; Andi Alfian Zainuddin; Rahmawati Minhajat1; Sri Jayanti (Faculty of Medicine, Hasanuddin University., 2024)
Introduction: Hepatitis C and B are two infectious diseases that increase distribution and high mortality and morbidity. Conditions that exacerbate the economic burden of these two viral hepatitis infections are complications of cirrhosis and gastrointestinal bleeding. This study sought to assess the risk levels of hepatitis C and B across various districts and cities in South Sulawesi. It involved identifying spatial clusters of affected individuals through an analytical model, employing Generalized Poisson Regression to evaluate the potential impacts of these viral infections. Methods: The natural break method is a quantifiable technique for identifying value clusters indicative of data distribution and for detecting geographical illness clusters, using Global Moran’s I statistics. This research utilizes data from health insurance members diagnosed with hepatitis C and B between January 2020 and December 2022, including 24 districts and cities in South Sulawesi Province. Results: According to the results of the Local Morans I analysis, there is no significant clustered hepatitis C and B in all districts and cities in South Sulawesi from 2020 until 2022. Conclusions: In South Sulawesi, the incidence of hepatitis C and B cases reported to National Social Health Insurance Administration Body (BPJS Kesehatan) appeared to manifest randomly or sporadically.